Safety verification of fatigue of bridges in reinforced concrete according to ABNT NBR 6118,2014 - Damo Rossato, Mateus; Da Silva Munhoz, Guilherme; Pereira dos Santos, Rúbia Bernadete; de Oliveira Scoz, Lucas Matheus (Revista ALCONPAT, 2021)
In this case study, the fatigue security of a bridge designed in 1987 was examined considering the current Brazilian standard. A structural model was developed to determine and verify fatigue security in the most critical section considering the Brazilian Load Model and the literature’s vehicle spectrum. According to the stress variation method, it concludes that the concrete submitted to compression meets the minimum criteria, but the steel section is not enough to resist shearing and flexural stresses. Pursuant to the Palmgren-Miner rule, the fatigue service life of the reinforcement’s bars under flexural stress is 14,91 years. A more detailed structural analysis of the bridge and the vehicle spectrum is necessary to confirm these results.